Au-doped zinc oxide nanostructure sensors for detection and discrimination of volatile organic compounds - Wongchoosuk C. (2014)
Pure and 10% w/w Au-doped zinc oxide (ZnO) nanostructure sensors were produced and used as sensing devices in a portable electronic nose (E-nose). The nanosensors were prepared using thermal oxidation technique with sintering temperature at 700°C under oxygen atmosphere at a flow rate of 500 mL min-1. The sensors were demonstrated to be sensitive to various volatile organic compounds (VOCs), especially ethanol vapour. The E-nose even with only two sensors was efficient to discriminate a number of selected VOCs. The Au-doped sensor shows a significant improvement of sensitivity. The portable E-nose can detect the difference between alcohol beverages and alcohol solutions and can distinguish the difference of white and red wines having the same percentage of alcohol. © W. S. Maney & Son Ltd. 2009.